THE ROLE OF CBCT IN THE EVALUATION OF PERIODONTAL DISEASES - Alexandra FOCHI (DUMITRESCU) (International Journal of Medical Dentistry, 2015)
Scope: Diagnosis of periodontal disease is firstly based on clinical signs and symptoms, however, when bone destruction is involved, radiographic examination is the most conclusive diagnosis method to be recommended. Even if the 2D radiography is most frequently used for such a diagnosis, CBCT (Cone Beam Computed Technology) comes to complete, help and provide new data on diagnosing periodontal lesions. The present study reviews original articles and synthesis papers issued between 2004-2014 in ScienceDirect, EBSCO, PubMed. Conclusions: In periodontology, CBCT appears as superior to 2D radiographies, being especially useful in the diagnosis of branch craters, lesions, vestibular and oral bone destructions, offering to the patient highly superior benefist compared to the risks caused by exposure.